Culture and Foreign Policy - Banús, Enrique (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
The Maastricht Treaty includes as the “second pillar” of the European Union a Common Foreign and Security Policy that is designed to improve co-operation in foreign policy, co-operation which has existed informally since 1970. However in recent times (for example, the Libyan crisis), the European nations have not found the single voice that has been expected of them. The article asks for the reasons for the difficulty in improving this policy. As hypothesis a linkage to culture is established, understood as values and attitudes but also memories and remembrances. The article explores the possibility that the differences in the foreign policy are linked with the long life of these elements in the collective mentality.

Traktat z Maastricht stworzył II filar Unii Europejskiej – Wspólną Politykę Zagraniczną i Bezpieczeństwa, która powstała w celu poprawieniu współpracy w zakresie polityki zagranicznej, współpracy, która istniała nieformalnie od 1970 roku. Mimo to ostatnio (na przykład w odniesieniu do kryzysu libijskiego) europejskie państwa nie znalazły wspólnego głosu, którego od nich oczekiwano. Przedmiotem artykułu jest pytanie o przyczyny trudności w udoskonalaniu tej polityki. Artykuł bada możliwość wynikania różnic w polityce zagranicznej z długiego okresu trwania tych elementów w mentalności zbiorowej.
Kultura i polityka zagraniczna
Keywords: Common Foreign Policy; Maastricht Treaty; stereotypes; political sciences; culture in European integration; Wspólna Polityka Zagraniczna; Traktat z Maastricht; stereotypy; nauki polityczne; kultura w integracji europejskiej